Theoretical approaches in the study of emotional literacy of primary students - Cristina KARABULUT (Acta et Commentationes, Sciences of Education, 2022)
The article contains theoretical interpretations on the evolution of the concept of emotional literacy, contributing to the formation of a general vision of the historical course of the term by which we understand a system of actions aimed at decoding the meaning of emotions and learning to effectively manage and channel emotional energy.